Lipid transfer protein sensitization: reactivity profiles and clinical risk assessment in an Italian cohort. Issue 8 (7th May 2015) - Scala, E.; Till, S. J.; Asero, R.; Abeni, D.; Guerra, E. C.; Pirrotta, L.; Paganelli, R.; Pomponi, D.; Giani, M.; De Pità, O.; Cecchi, L.
Abstract Background Nonspecific lipid transfer proteins (nsLTPs) represent a major cause of systemic food allergic reactions in the Mediterranean area. This study investigate hierarchical patterns and cluster relationships of IgE sensitization to different nsLTPs, and the relationship to clinical allergy in a large Italian cohort. Methods A total of 568 nsLTP‐positive subjects after IgE ImmunoCAP‐ISAC microarray analysis with Ara h 9, Art v 3, Cor a 8, Jug r 3, Pla a 3, Pru p 3 and Tri a 14 allergens were studied. IgE inhibition experiments were carried out with mugwort and plane tree pollen extracts. Results Eighty‐two per cent of nsLTP‐positive participants (94% if <6 years old) were Pru p 3pos, and 71% were Jug r 3pos. Participants who reacted to >5 nsLTPs reported a higher incidence of food‐induced systemic reactions. Only Art v 3 and Pla a 3 (mugwort and plane tree nsLTPs, respectively) were associated with respiratory symptoms, and a correlation was observed between sensitization to pollen and plant food nsLTPs, particularly between Pla a 3 and tree nut/peanut nsLTPs. Co‐sensitization to Par j 2 and PR‐10 or profilin pan‐allergens was associated with a lower prior prevalence of severe food‐induced reactions. In inhibition assays, plane and mugwort pollen extracts inhibited 50–100% of IgE binding to food nsLTPs in microarrays. Conclusions Testing IgE reactivity to a panel of nsLTP allergens unveils important associations between nsLTP sensitization profiles and clinical presentation and allows the identification of novel cluster patterns indicating likely cross‐reactivities and highlighting potential allergens for nsLTP immunotherapy.